Temperate forest. - Woodward, John (Austin, TX : Raintree Steck-Vaughn, 2002)
A comprehensive look at the temperate forest biome, examining its climate, plants, animals, people, and future, plus detailed views of some famous or important temperate locations.
Keywords: Forest ecology; Temperate climate